The political economy of social violence: theory and evidence from a cross-country study - Fox, Sean (2010)
Why are some countries more prone to social violence than others? Drawing on theoretical and empirical insights from the fields of political economy, sociology and criminology we develop and empirically test a holistic theory of social violence that accounts for political-institutional, socio-economic and socio-demographic factors. We find that hybrid political regimes, political-institutional volatility, poverty, inequality and ethnic diversity are associated with higher rates of social violence. Unexpectedly, higher rates of economic growth are also found to be robustly correlated with higher rates of social violence